ANALISA PENGARUH KENAIKAN TARIF PPN 12% DAN FOMO (FEAR OF MISSING OUT) TERHADAP PENGELOLAAN KEUANGAN PRIBADI GEN Z DI SURABAYA DIMEDIASI TEKNOLOGI AI - Pertiwi, Aulia Citra; Wany, Eva (Ekomania, 2024)
This research aims to analyze the impact of the 12% VAT rate increase and FoMO (Fear of Missing Out) on the Personal Financial Management of Gen Z in Surabaya, mediated by AI Technology. The method used in this research is descriptive quantitative. 44 Gen Z in the city of Surabaya are the sample, which was selected using purposive sampling.After data collection through questionnaires, SmartPLS was used to analyze the data. The research results show that among Gen Z, the increase in the VAT rate to 12% does not have a significant impact on personal financial management, while FoMO has a significant impact on personal financial management. Meanwhile, AI Technology